Patterns of Vestibular Impairment in Bilateral Vestibulopathy and Its Relation to Etiology - van Stiphout, Lisa; Pleshkov, Maksim; Lucieer, Florence; Dobbels, Bieke; Mavrodiev, Vergil; Guinand, Nils; Pérez Fornos, Angelica; Widdershoven, Josine; Strupp, Michael; Van Rompaey, Vincent; van de Berg, Raymond (Frontiers in Neurology, 2022)
Objective This study aimed to investigate 1) the patterns of vestibular impairment in bilateral vestibulopathy (BVP) and subsequently the implications regarding patient eligibility for vestibular implantation, and 2) whether this pattern and severity of vestibular impairment is etiology dependent. Methods One hundred and seventy-three subjects from three tertiary referral centers in Europe were diagnosed with BVP according to the Bárány Society diagnostic criteria. Subjects underwent vestibular testing such as the caloric test, torsion swing test, three-dimensional or horizontal video Head Impulse Test (vHIT), and cervical and/or ocular vestibular evoked myogenic potentials (c- and oVEMPs). The etiologies were split into idiopathic, genetic, ototoxicity, infectious, Menière’s Disease, (head)trauma, auto-immune, neurodegenerative, congenital, and mixed etiology. Results The caloric test and horizontal vHIT more often indicated horizontal semicircular canal impairment than torsion swing test. Three-dimensional vHIT results showed significantly higher gains for both anterior canals compared with horizontal and posterior canals (p<0.001). Rates of bilaterally absent oVEMP responses were higher compared to bilaterally absent cVEMP responses (p=0.010). Fifty-four percent of the patients diagnosed with BVP without missing data met all three Bárány Society diagnostic test criteria, whereas 76% of the patients were eligible for implantation according to the vestibular implantation criteria. Regarding etiology, only horizontal vHIT results were significantly lower for trauma, neurodegenerative and genetic disorders, whereas horizontal vHIT results were significantly higher for Menière’s Disease, infectious and idiopathic BVP. Exploration with hierarchical cluster analysis showed no significant association between etiology and patterns of vestibular impairment. Conclusion This study showed that caloric testing and vHIT seem to be more sensitive for measuring vestibular impairment, whereas torsion swing test is more suited for measuring residual vestibular function. In addition, no striking patterns of vestibular impairment in relation to etiology were found. Nevertheless, it was demonstrated that although the implantation criteria are more strict compared with the Bárány Society diagnostic criteria, still 76% of BVP patients were eligible for implantation based on vestibular test criteria. It is advised to carefully examine every patient for their overall pattern of vestibular impairment, in order to make well informed and personalized therapeutic decisions.